Chemical analysis and anti-proliferative activity of Campania Thymus Vulgaris essential oil. Issue 6 (2nd November 2017) - Catauro, Michelina; Bollino, Flavia; Tranquillo, Elisabetta; Sapio, Luigi; Illiano, Michela; Caiafa, Ilaria; Naviglio, Silvio
Abstract: In this study, the potential antitumor activity of an essential oil (EO) obtained from Thymus vulgaris L. plants cultivated in Campania (Southern Italy) was evaluated. The gas chromatography-mass spectrometry and Fourier transform infrared spectroscopy were used to investigate the chemical composition of EO. The monoterpenes thymol, p-cymene and carvacrol are the more abundant compounds detected. The anti-proliferative activity of the EO as a function of dose and time of exposure was evaluated by MTT assay on human osteosarcoma U2OS and pancreatic cancer PANC-1 cell lines. EO inhibits proliferation of both cell lines, but the effect on PANC-1 cells was more extensive. Flow cytometry and Western blot analyses revealed that the anti-proliferative effect is due to a decrease of cells in the S phase and their accumulation in the G1 phase, associated with the decrease of cyclin A and the increase of cell cycle inhibitor p27 protein levels, respectively.